First-principles study of the structural, electronic, dynamical, and mechanical properties of Pd–Nb binary systems. (September 2022) - Liu, Mingfeng; Wang, Lei; Wang, Jiantao; Zhu, Heyu; Ma, Hui; Wei, Yan; Zhang, Aimin; Chen, Li; Liu, Peitao; Chen, Xing-Qiu
Abstract: We study the structural, electronic, dynamical, and mechanical properties of the whole Pd–Nb binary systems based on first-principles density functional theory calculations. Using the variable-composition evolutionary structure search algorithm, we predict five new ground-state phases (cI32-Pd15 Nb, oF60-Pd13 Nb 2, mC24-Pd 5 Nb, oC16-PdNb 7, and oC32-PdNb15 ) and nine metastable phases (oC24-Pd11 Nb, mC18-Pd 8 Nb, hP9-Pd 8 Nb, mC12-Pd 5 Nb, tP2-PdNb, oC20-PdNb, tI10-Pd 2 Nb 3, oC20-Pd 2 Nb 3, and mP10-PdNb 4 ) that have not yet been either experimentally reported or theoretically predicted. All the predicted phases are dynamically stable in the absence of soft phonon modes in calculated phonon dispersions. The elastic properties calculations show that all these compounds are also mechanically stable. We find that the Young's modulus, bulk modulus as well as shear modulus exhibit similar convex variations with respect to the Nb concentrations, while the Poisson's ratio shows the opposite trend. These trends are found to be highly correlated with the atomic arrangement in crystal structures and associated chemical bondings. Among all the predicted Pd x Nb y compounds, tI8-Pd 3 Nb exhibits the largest elastic moduli due to its relatively close-packed structure induced near homogeneous chemical bondings. The electronic structure calculations reveal that all predicted Pd–Nb compounds are metallic with complex band structures. Interestingly, the oI6-Pd 2 Nb compound hosts nontrivial Dirac nodal lines around the Fermi energy and exhibits topological nodal line surface states on the (001) plane. This work provides the first complete survey on the whole Pd–Nb systems, paving the way to exploring potential candidates for Pd-based electrocatalysts.